2009
DOI: 10.1177/104063870902100618
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Age and Sex of Rocky Mountain Elk (Cervus Elaphus Nelsoni) on Follicle Counts from Rectal Mucosal Biopsies for Preclinical Detection of Chronic Wasting Disease

Abstract: Abstract. To determine if the number of rectal lymphoid follicles decreases with respect to age and sex relative to diagnosis of chronic wasting disease (CWD), rectal biopsies (n 5 1,361) were taken from captive Rocky Mountain elk (Cervus elaphus nelsoni) at 4 ranches in the western United States between 2005 and 2008. Rectal tissues were stained with a monoclonal antibody (F99/97.6.1), which selectively stains the abnormal isoform of the prion protein associated with CWD of elk. The number of lymphoid follicl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 12 publications
(34 reference statements)
1
4
0
Order By: Relevance
“…7 Fewer lymph follicles are also found within rectal biopsy samples collected from older animals. 3,16 In the present study, the percentage of samples with an insufficient number of follicles occurred at an unexpectedly high rate (44%) in Canada herd 3, while the other 3 herds had rates of 9–17%, which is similar to a previous study. 7 Because the procedure causes minimal discomfort to the animal, the procedure is often performed using only restraint in proper animal handling facilities and topical anesthesia.…”
Section: Discussionsupporting
confidence: 90%
“…7 Fewer lymph follicles are also found within rectal biopsy samples collected from older animals. 3,16 In the present study, the percentage of samples with an insufficient number of follicles occurred at an unexpectedly high rate (44%) in Canada herd 3, while the other 3 herds had rates of 9–17%, which is similar to a previous study. 7 Because the procedure causes minimal discomfort to the animal, the procedure is often performed using only restraint in proper animal handling facilities and topical anesthesia.…”
Section: Discussionsupporting
confidence: 90%
“…It has been tentatively suggested that at least 10 follicles are needed to obtain accurate diagnostic results from a rectal biopsy (Spraker et al, 2009a, b). Because follicle counts decline with age, most samples from elk that are older than 8 yr cannot meet this requirement (Spraker et al, 2009a). We suggest that for population-level inferences there is no need to obtain a minimum number of follicles because modern methods of hierarchic modeling (Clark and Gelfand, 2006) allow uncertainty associated with diagnosis to be included in a statistically appropriate way to estimate quantities of interest such as prevalence (see also Wolfe et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…To date, preclinical testing for PrP CWD utilizes immunohistochemistry (IHC) of the palatine tonsils or rectal lymphoid tissues in cervids. 18,21,24 However, IHC does not routinely detect very early cases of CWD in these tissues. 17,20 Various fluids, such as saliva, blood, urine, and cerebrospinal fluid (CSF) have been evaluated in animals for their use in preclinical antemortem detection of abnormal prions.…”
mentioning
confidence: 99%